PERANAN Musca domestica SEBAGAI VEKTOR MEKANIK TELUR INFEKTIF Ascaris lumbricoides - Suriyani Tan; Machrumnizar Machrumnizar (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2017)
Muscadomestica (house fly) is an insect that is considered useless by humans although they lived very close to humans. Breeding site of flies in human or animal waste, the rubbish, or unorganic objects that have decayed greatly support their role as mechanical vectors. More than 20 species of flies have been reported as an agent of gastrointestinal diseases. The purpose of this study is to examnine the role of houseflies as mechanical vectors Ascarislumbricoides’seggs.The research sample was 500 house flies (Muscadomestica) captured in the Legok area. Houseflies were trapped by fly trap containing rotten fish meat and then stored at a temperature of 4 degree celcius. The samples were divided into six groups according to the sampling areas, crushed and checked directly by using a light microscope. Ascarislumbricoides eggs are not found in all groups of samples. The study concluded that Muscadomestica is not a mechanical vector of infective eggs of Ascarislumbricoides in Tangerang City, Banten Province.